Increasing Public Awareness: Socialization of the Dangers of Online Gambling in Dadaprejo Village and Bullying Prevention at Al-Firdaus Vocational School, Malang - Eka Puspa Wardani; Risky Angga Pramuja; Siska Adi Yuliana; Rizka Winda Pratiwi; Ahmad Bagas Triwardana; Bimaa Marksyriifan Akbar (Jurnal Insan Pengabdian Indonesia, 2024)
: Community Service by Students (PMM) is a real form of implementation of higher education values ​​to contribute to society. PMM Group 45 Wave 3 of the University of Muhammadiyah Malang carried out two socialization activities that focused on crucial issues in society, namely the dangers of online gambling and bullying. This socialization was held in two different locations: Dadaprejo Village and Al Firdaus Vocational School. The aim is to increase public and student awareness of the negative impacts caused by online gambling and bullying. Through interactive discussions and in-depth delivery of materials, this activity is expected to increase understanding, change mindsets, and encourage positive actions from all parties involved. With support from previous research, this socialization activity shows the importance of the role of education in reducing social risks faced by society and students.